Whatsapp and Wordplay: Gamified English Learning in Nonformal Classroom - Dina Fitria; Sujito (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
English vocabulary mastery presents a significant challenge for nonformal education students characterized by heterogeneous backgrounds and limited face-to-face instructional time. This study explores the effectiveness of gamified vocabulary challenges through WhatsApp in improving vocabulary mastery among Grade XI students at PKBM Arrohmah Demak Package C program. Employing a pre-experimental design with one-group pretest-posttest, the research involved 40 students participating in a two-week gamification program with structured daily and weekly tasks. Data were collected through standardized vocabulary tests and participation tracking via WhatsApp platform. Analysis using paired sample t-test and Pearson correlation revealed significant improvement in mean scores from 56.2 to 74.8 with participation rates reaching 87.5%. The multidimensional assessment system measured timeliness, completeness, accuracy, and creativity with an overall achievement of 77.4%. A strong positive correlation was identified between participation levels and learning achievement. Findings confirm that integrating gamification and mobile learning through WhatsApp effectively enhances vocabulary mastery in nonformal education contexts. This platform offers high accessibility and flexibility suitable for adult learner characteristics. Despite its effectiveness, challenges such as limited internet access and low student creativity require attention in future digital learning implementations.